INDIVIDUALIZATION OF PROFESSIONALLY ORIENTED EDUCATION AS A BASIS FOR IMPROVING THE EFFICIENCY OF STUDY FOREIGN LANGUAGES IN HIGHER PEDAGOGICAL INSTITUTIONS - Мелікова, С. О. (Pedagogy of Higher and Secondary Education, 2011)
The problem of improvement of students’ prifessional oriented learning effectiveness at non-linguistics specialities in the Higher Pedagogical School is examined. The authour considers individualization of the professional oriented learning of foreign languages as the basis of the current educational process.